Genome-wide analysis reveals the extent of EAV-HP integration in domestic chicken. (December 2015) - Wragg, David; Mason, Andrew; Yu, Le; Kuo, Richard; Lawal, Raman; Desta, Takele; Mwacharo, Joram; Cho, Chang-Yeon; Kemp, Steve; Burt, David; Hanotte, Olivier
Abstract Background EAV-HP is an ancient retrovirus pre-datingGallus speciation, which continues to circulate in modern chicken populations, and led to the emergence of avian leukosis virus subgroup J causing significant economic losses to the poultry industry. We mapped EAV-HP integration sites in Ethiopian village chickens, a Silkie, Taiwan Country chicken, red junglefowlGallus gallus and several inbred experimental lines using whole-genome sequence data. Results An average of 75.22 ± 9.52 integration sites per bird were identified, which collectively group into 279 intervals of which 5 % are common to 90 % of the genomes analysed and are suggestive of pre-domestication integration events. More than a third of intervals are specific to individual genomes, supporting active circulation of EAV-HP in modern chickens. Interval density is correlated with chromosome length (P  < 2.31−6 ), and 27 % of intervals are located within 5 kb of a transcript. Functional annotation clustering of genes reveals enrichment for immune-related functions (P  < 0.05). Conclusions Our results illustrate a non-random distribution of EAV-HP in the genome, emphasising the importance it may have played in the adaptation of the species, and provide a platform from which to extend investigations on the co-evolutionary significance of endogenous retroviral genera with their hosts.